2020
DOI: 10.3390/ijerph17103623
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Melatonin as Predictors of Cognitive, Emotional and Functional Ageing of Older People

Abstract: Background: The ageing process causes a number of changes in the human immune and endocrine systems. The aim of this study was to assess the relationship between cognitive, emotional and functional skills as well lifestyle, versus selected biochemical indicators of the ageing process. Methods: The cross-sectional study was conducted in a group of 121 people aged 60–90 residing in the Lesser Poland voivodship. The study used standardized research tools including the Barthel scale, Instrumental Activities of Dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
6
Order By: Relevance
“…Aging is characterized as a complex process, resulting from several interactions between biological, psychological, and social factors, which can contribute in different ways to trace different trajectories of aging. Indeed, each of these components may concur as a protective factor towards physiological, or even to a successful, aging, as well as a vulnerability factor that progressively exposes the individual to reduced independence [ 56 ] and increased risk of adverse age-related outcomes [ 57 , 58 , 59 , 60 ]. Therefore, the implementation of preventive strategies should be aimed at facing the consequences of the pandemic not only on the physical health of the elderly [ 61 ] but also on their HRQoL and their psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is characterized as a complex process, resulting from several interactions between biological, psychological, and social factors, which can contribute in different ways to trace different trajectories of aging. Indeed, each of these components may concur as a protective factor towards physiological, or even to a successful, aging, as well as a vulnerability factor that progressively exposes the individual to reduced independence [ 56 ] and increased risk of adverse age-related outcomes [ 57 , 58 , 59 , 60 ]. Therefore, the implementation of preventive strategies should be aimed at facing the consequences of the pandemic not only on the physical health of the elderly [ 61 ] but also on their HRQoL and their psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, another study showed that low serum melatonin was associated with autonomic neuropathy in type 2 diabetic patients and indicated that the circadian rhythm of melatonin secretion is blunted in type 2 diabetic patients [ 17 ]. Similarly, reduced melatonin was also associated with cognitive dysfunction in patients with Alzheimer's disease, schizophrenia, and even healthy older people [ 7 , 18 , 19 ]. However, it remains unclear about the association between serum melatonin and MCI in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, melatonin alleviates cognitive disturbance resulting from breast cancer chemotherapy ( 124 )). Recent advances have regarded melatonin as an index of cognitive impairment in elderly individuals ( 125 ). Moreover, melatonin has been shown to effectively improve cognitive deficits in AD mouse models ( 126 ).…”
Section: Melatonin Improves Mood and Cognitive Functionmentioning
confidence: 99%